Erotic Devotion and Theological Strain in Contemporary Indonesian Islamic Fiction - Shofah, Novia Adibatus; Indriyani, Jiphie Gilia; Septiyani, Rizki Endi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This article examines the intersection of erotic desire and religious devotion in Emha Ainun Nadjib’s BH, a contemporary Indonesian Islamic short story that challenges conventional theological boundaries. The narrative centres on two male characters. First is Niken, a feminised transgender figure, and second is Aku, a devout Muslim man, whose relationship embodies homoerotic intimacy intertwined with spiritual tension. Drawing on Judith Butler’s theory of gender performativity, the study explores how Islamic values and moral expectations shape expressions of queer desire. Using a qualitative descriptive method and close textual analysis, the research reveals that Niken openly enacts her gender identity through stylised feminine expression, signifying confidence and spiritual acceptance of her queer self. In contrast, Aku displays restrained masculinity and emotional detachment, illustrating an internal theological struggle between piety and same-sex longing. These contrasting performances expose the theological strain experienced by queer Muslim individuals in reconciling erotic devotion with religious conformity. The study argues that BH offers a literary space where Islamic belief and homoerotic intimacy collide, complicating the boundaries between sacred and profane. By examining such tensions in Islamic fiction, the article contributes to broader conversations on gender, sexuality, and spirituality in contemporary Indonesian literature.